2023
DOI: 10.2147/jpr.s397064
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Measurement Properties of Face, Legs, Activity, Cry and Consolability Scale for Pediatric Pain Assessment

Abstract: Purpose We performed this systematic review to summarize the psychometric properties of Face, Legs, Activity, Cry and Consolability ( FLACC ) scale in pediatric patients in different settings. Methods Two investigators independently searched PubMed, EMBASE, OVID and China National Knowledge Infrastructure (CNKI) for eligible studies through July 2021. We assessed the psychometric properties using the modified critical appraisal tool (CAT). Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Postoperative analgesia was assessed by the FLACC scale which is moderately reliable for patients aged between 5 and 16 years. 4 SR Engineer et al found that replacing clonidine in place of epidural fentanyl resulted into comparable analgesia with fewer side effects. Tsui and Charles, showed that ketamine or clonidine to a caudal epidural prolong the duration of block.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative analgesia was assessed by the FLACC scale which is moderately reliable for patients aged between 5 and 16 years. 4 SR Engineer et al found that replacing clonidine in place of epidural fentanyl resulted into comparable analgesia with fewer side effects. Tsui and Charles, showed that ketamine or clonidine to a caudal epidural prolong the duration of block.…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative pain was assessed using the face, legs, activity, cry, and consolability (FLACC) pain scale (Table 1), and the sedation score was assessed using Ramsay sedation score (Table 2). 4 The surgical procedures done performed included primary bladder closure, anterior abdominal wall closure, pelvic osteotomy, ureteric re-implantation, bladder neck repair, epispadias repair, and vaginal reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, self-report pain assessment scales such as visual analog scale (VAS) depends on choosing the face that has expressions that highly represent the child's pain perception [11]. In addition, FLACC (Face, Legs, Activity, Cry, Consolability) scale is an objective scale in which facial expressions are taken into consideration while detecting the pain intensity [12].…”
Section: Introductionmentioning
confidence: 99%